Black cultural studies is intersectionality. (November 2020) - Johnson, Marcus; Joseph, Ralina L
This article argues that Black cultural studies must be understood as an intersectional intervention of praxis. Grounding our field in the past, speaking from the present, and projecting to the future, we examine the transformational influence that Black feminist theory has had on cultural studies, from Kimberlé Williams Crenshaw's defense of 2 Live Crew, to the #SayHerName and Protect Black Women rally and marches.